Indikator Kesiapan Klien Dalam Bimbingan Konseling: Tinjauan Literatur Dan Implikasinya Bagi Praktik Konseling - Okti, Diana Rezu; M, Mudjiran; Karneli, Yeni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Client readiness is a key factor influencing success in the counseling guidance process. This article presents a literature review related to indicators of client readiness that are important in determining the effectiveness of counseling. Various studies have shown that client readiness can be influenced by internal factors, such as personal motivation, self-awareness, and emotional readiness, as well as external factors, such as social support and life situations faced. This article identifies key indicators of client readiness, including openness to change, ability to recognize problems, and commitment to be actively involved in the counseling process. In addition, the implications of these indicators for counseling practice are also discussed, including the importance for counselors to develop appropriate strategies in assessing and facilitating client readiness. By understanding indicators of client readiness, counseling practitioners can design more effective interventions that focus on increasing client motivation and involvement. This article is expected to provide useful insights for counselors and researchers to better understand the dynamics of client readiness and its application in more optimal counseling practice.